From 2D to 3D video conferencing: modular RGB-D capture and reconstruction for interactive natural user representations in immersive extended reality (XR) communication - Gunkel, Simon N. B.; Dijkstra-Soudarissanane, Sylvie; Stokking, Hans M.; Niamut, Omar A. (Frontiers in Signal Processing, 2023)
With recent advancements in Virtual Reality (VR) and Augmented Reality (AR) hardware, many new immersive Extended Reality (XR) applications and services arose. One challenge that remains is to solve the social isolation often felt in these XR experiences and to enable a natural multi-user communication with high Social Presence. While a multitude of solutions exist to address this issue with computer-generated ``artificial" avatars (based on pre-rendered 3D models), this form of user representation might not be sufficient for conveying a sense of co-presence for many use cases. In particular, for personal communication (for example, with family, doctor, or sales representatives) or for applications requiring photorealistic rendering. One alternative solution is to capture users (and objects) with the help of RGBD sensors to allow real-time photorealistic representations of users. In this paper, we present a complete and modular RGBD capture application and outline the different steps needed to utilize RGBD as means of photorealistic 3D user representations. We outline different capture modalities, as well as individual functional processing blocks, with its advantages and disadvantages. We evaluate our approach in two ways, a technical evaluation of the operation of the different modules and two small-scale user evaluations within integrated applications. The integrated applications present the use of the modular RGBD capture in both AR and VR communication application use cases, tested in realistic real-world settings. Our examples show that the proposed modular capture and reconstruction pipeline allows for easy evaluation and extension of each step of the processing pipeline. Furthermore, it allows parallel code execution, keeping performance overhead and delay low. Finally, our proposed methods show that an integration of 3D photorealistic user representations into existing video communication transmission systems is feasible and allows for new immersive XR applications.